Change the fraction to a improper fraction.
11/9 + 10/9
Since they have the same denominators you can add them.
11/9 + 10/9 = 21/9
The answer is 21/9
Hope this helps :)
Answer:
- y = 2x + 3
- y = -6x
- y = -x + 2
- y = 2x - 7
Step-by-step explanation:
<u>Slope-intercept form:</u>
<em>Hint. if we have x = 0, then the y-coordinate is the same as b</em>
<u>Slope</u>
33.
- m = (9 -(-3))/(3 - (-3)) = 12/6 = 2
- b = 3 as per table (0, 3)
34.
- m = (0-12)/(0 - (-2)) = -12/2 = -6
- b = 0, as per table (0, 0)
35.
- m = (2 - (-2))/(0 - 4) = 4/-4 = -1
- b = 2, as per table (0, 2)
36.
- m = (-5 - (-1))/ (1 -3) = -4/-2 = 2
Using point (3, -1)
- -1 = 2*3 + b
- b= -1 - 6= - 7
Answer:
y=4x-13
Step-by-step explanation:
<span>given that P(x) --->p(x+6)+3
</span>
∴ x will become x+6
and P(x+6) will become P(x+6)+3
<span />
So, The graph of [p(x+6)+3] will be the same as the graph of [p(x)] but shifted 6 units to the left then shifted 3 units up
OR by another words, we need to make axis translations from (0,0) to (-6,3)